“LOGISMOI”, VISIONE, ALLUCINAZIONE: UN FONDAMENTO TEOLOGICO - BUZALIC, Alexandru (Studia Universitatis Babeș-Bolyai Theologia Catholica, 2019)
Logismoi, vision, hallucination: theological foundations. Demonology as an autonomous discipline of dogmatic theology or as part of angelology or theology of creation, deals with the presence of evil spirits and their action in the world. The action of demons becomes perceptible only through the spiritual life as a struggle against the powers that seek to corrupt them by the way of salvation. But man, a material-spiritual entity, has to deal with the endogenous causes that are specific to the human condition, with suggestions that become unfavorable through the way the individual transforms them through scruples that generate obsessions. The spiritual masters of the Church were fine observers and separated the intervention of the demons from the beginnings of the fallen human condition. At present, in the light of positive disciplines that directly or tangentially touch on issues of interest in the field of demonology, we can base the theological aspects taking into account the development of the psychology of religion, psychopathology, psychotherapy or psychiatry. Logismoi, viziune, halucinație: un fundament teologic. Demonologia ca disciplină autonomă a teologiei dogmatice sau ca parte a angelologiei sau teologiei creației, se ocupă de prezența spiritelor rele și de acțiunea lor în lume. Acțiunea demonilor devine perceptibilă numai prin viața spirituală, ca luptă împotriva puterilor care încearcă să-i corupă de la mântuire. Dar omul, o entitate material-spirituală, trebuie să se ocupe de cauzele endogene specifice condiției umane, cu sugestii care devin nefavorabile în modul în care individul le transformă prin scrupule care generează obsesii. Maeștrii spirituali ai Bisericii au fost observatori excelenți și au separat intervenția demonilor de pulsiunile condiției umane căzute. La ora actuală, în lumina disciplinelor pozitive care ating direct sau tangențial chestiuni de interes în domeniul demonologiei, putem baza aspectele teologice ținând cont de dezvoltarea psihologiei religiei, a psihopatologiei, a psihoterapiei sau a psihiatriei. Cuvinte-cheie: Biserică, demonologie, „logismoi”, halucinații, sugestii, viziune, viață spirituală